A Managed Care System with Telemedicine Support for Neurological Emergencies. Issue 3 (2nd December 2022) - Erdur, Hebun; Weber, Joachim E.; Angermaier, Anselm; Kinze, Stephan; Sotoodeh, Ali; Gorski, Claudia; Bollweg, Kerstin; Ernst, Stefanie; Kandil, Farid I.; Behrens, Janina; Ganeshan, Ramanan; Keysers, Anne; et al.
Abstract : Objectives: Telemedicine is frequently used to provide remote neurological expertise for acute stroke workup and was associated with better functional outcomes when combined with a stroke unit system‐of‐care. We investigated whether such system‐of‐care yields additional benefits when implemented on top of neurological competence already available onsite. Methods: Quality improvement measures were implemented within a "hub‐and‐spoke" teleneurology network in 11 hospitals already provided with onsite or telestroke expertise. Measures included dedicated units for neurological emergencies, standardization of procedures, multiprofessional training, and quality‐of‐care monitoring. Intervention effects were investigated in a controlled study enrolling patients insured at 3 participating statutory health insurances diagnosed with acute stroke or other neurological emergencies. Outcomes during the intervention period between November 2017 and February 2020 were compared with those pre‐intervention between October 2014 and March 2017. To control for temporal trends, we compared outcomes of patients with respective diagnoses in 11 hospitals of the same region. Primary outcome was the composite of up‐to‐90‐day death, new disability with the need of ambulatory or nursing home care, expressed by adjusted hazard ratio (aHR). Results: We included 1, 418 patients post‐implementation (55% female, mean age 76.7 ± 12.8 year) and 2, 306 patients pre‐implementation (56%, 75.8 ± 13.0 year, respectively). The primary outcome occurred in 479/1, 418 (33.8%) patients post‐implementation and in 829/2, 306 (35.9%) pre‐implementation. The aHR for the primary outcome was 0.89 (95% confidence interval [CI]: 0.79–0.99, p = 0.04) with no improvement seen in non‐participating hospitals between post‐ versus pre‐implementation periods (aHR 1.04; 95% CI: 0.95–1.15). Interpretation: Implementation of a multicomponent system‐of‐care was associated with a lower risk of poor outcomes. ANN NEUROL 2023;93:511–521